Functional and structural characterization of the Methanosarcina mazei proteasome and PAN complexes. - Medalia, N; Sharon, M; Martinez-Arias, R; Mihalache, O; Robinson, C; Medalia, O; Zwickl, P (2006)
We have cloned the proteasome and the proteasome activating nucleotidase (PAN) genes from the mesophilic archaeon Methanosarcina mazei and produced the respective proteins in Escherichia coli cultures. The recombinant complexes were purified to homogeneity and characterized biochemically, structurally, and by mass spectrometry. We found that the degradation of Bodipy-casein by Methanosarcina proteasomes was activated by Methanosarcina PAN. Notably, the Methanosarcina PAN unfolded GFP-SsrA only in the presence of Methanosarcina proteasomes. Structural analysis by 2D averaging electron microscopy of negatively stained complexes displayed the typical structure for the proteasome, namely four-striped side-views and sevenfold-symmetric top-views, with 15 nm height and 11 nm diameter. The structural analysis of the PAN preparation revealed also four-striped side-views, albeit with a height of 18 nm and sixfold-symmetric top-views with a diameter of 15 nm, which corresponds most likely to a dimer of two hexameric complexes. Mass spectrometric analysis of both the Methanosarcina and the Methanocaldococcus PAN proteins indicated hexameric complexes. In summary, we performed a functional and structural characterization of the PAN and proteasome complexes from the archaeon M. mazei and described unique new structural and functional features.